Inspiring, Educating, and Integrating Islamic Values through Community Service Program (KKN) Activities in Timpeh and Kamang Baru Districts - Bella Saprilla; Haliamah Andi Saputri; Andini Regika Putri; Lisa Ningsih; Diva Miftahul Jannah; B.R.E Yunanda (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The Community Service Program (KKN) is a form of community service carried out by students as an implementation of the Tri Dharma of Higher Education. This program aims to improve student competency while making a real contribution to the community. The KKN program, implemented in Timpeh and Kamang Baru Districts, carried the theme